Microstructure and mechanical behaviour of additive manufactured Ti–6Al–4V parts under tension - Panin Alexey; Kazachenok Marina; Kolmakov Alexey; Chizhik Sergey; Heifetz Mikhail; Chugui Yuri (EPJ Web of Conferences, 2019)
Metal-based additive manufacturing technologies using electron or laser beams as a heat source for melting a metal powder or wire have been the subject of keen interest in recent years. At present paper a comparative analysis of the microstructure, strain response during tensile test and mechanical properties of Ti–6Al–4V samples produced by selective laser melting, electron beam melting or electron beam free-form fabrication were performed. A microstructural study using transmission electron microscopy revealed columnar prior β grains transformed into a lamellar α-morphology in the samples. According to X-ray diffraction study, the volume fractions of the β-Ti phase in the samples were equal to 2, 4 and 6 % respectively. It has been shown that the Vickers microhardness of SLM and EBM Ti–6Al–4V samples was similar (~5.4 GPa) while the hardness of EBF3 parts was significantly lower (4.5 GPa). The uniaxial stress-strain response of the Ti–6Al–4V samples fabricated by different additive manufacturing technologies were compared. Crystallographic (dislocation motion) and non-crystallographic (shear banding) deformation mechanisms of the loaded samples were studied by scanning electron microscopy and optical profilometry.